Submicron sized water-stable metal organic framework (bio-MOF-11) for catalytic degradation of pharmaceuticals and personal care products - Azhar, M.; Vijay, P.; Tade, Moses; Sun, Hongqi; Wang, Shaobin (Elsevier, 2018)
Water-stable and active metal organic frameworks (MOFs) are important materials for mitigation of water contaminants via adsorption and catalytic reactions. In this study, a highly water-stable Co-based MOF, namely bio-MOF-11-Co, was synthesized by a simplified benign method. Moreover, it was used as a catalyst in successful activation of peroxymonsulfate for catalytic degradation of sulfachloropyradazine (SCP) and para-hydroxybenzoic acid (p-HBA) as representatives of pharmaceuticals and personal care products, respectively. The bio-MOF-11-Co showed rapid degradation of both p-HBA and SCP and could be reused multiple times without losing the activity by simply water washing. The effects of catalyst and PMS loadings as well as temperature were further studied, showing that high catalyst and PMS loadings as well as temperature produced faster kinetic degradation of p-HBA and SCP. The generation of highly reactive [Figure presented] and HO[rad] radicals during the degradation was investigated by quenching tests and electron paramagnetic resonance. A plausible degradation mechanism was proposed based on the functionalities in the bio-MOF-11-Co. The availability of electron rich nucleobase adenine reinforced the reaction kinetics by electron donation along with cobalt atoms in the bio-MOF-11-Co structure.